2020
DOI: 10.1001/jamanetworkopen.2020.7426
|View full text |Cite
|
Sign up to set email alerts
|

Association of Medicaid Eligibility With Surgical Readmission Among Medicare Beneficiaries

Abstract: IMPORTANCE The Centers for Medicare & Medicaid Services is beginning to consider adjusting for social risk factors, such as dual eligibility for Medicare and Medicaid, when evaluating hospital performance under value-based purchasing programs. It is unknown whether dual eligibility represents a unique domain of social risk or instead represents clinical risk unmeasured by variables available in traditional Medicare claims. OBJECTIVE To assess how dual eligibility for Medicare and Medicaid is associated with ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
(107 reference statements)
1
11
0
Order By: Relevance
“…In general surgery populations, adjusting for DCI was associated with improved performance of the American College of Surgeons National Surgical Quality Improvement Program risk calculator, which is composed solely of clinical and demographic factors. 4,5 Notably, the application of the cost element of scoring was deferred in the first year of MIPS. An early analysis of the Comprehensive Joint Replacement program, a pilot of surgical bundled payment, demonstrated that cost savings were primarily achieved through reduced use of posthospital care, services that patients with low socioeconomic status required more frequently.…”
Section: Conflict Ofmentioning
confidence: 99%
“…In general surgery populations, adjusting for DCI was associated with improved performance of the American College of Surgeons National Surgical Quality Improvement Program risk calculator, which is composed solely of clinical and demographic factors. 4,5 Notably, the application of the cost element of scoring was deferred in the first year of MIPS. An early analysis of the Comprehensive Joint Replacement program, a pilot of surgical bundled payment, demonstrated that cost savings were primarily achieved through reduced use of posthospital care, services that patients with low socioeconomic status required more frequently.…”
Section: Conflict Ofmentioning
confidence: 99%
“…12 Our results are consistent with previous research that has shown poorer outcomes in DE patients. [7][8][9][10][11] Higher rates of complications and nonhome discharge have important implications for DE patients undergoing cancer treatment because previous research has shown these are risk factors for delayed chemotherapy and worse survival. [32][33][34] However, our analysis builds on these findings by examining the role of hos-pital quality in mitigating these disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Although the direct cause of the association between primary JAMA Network Open | Surgery payer and risk of PPR cannot be ascertained using this data source, previous studies have shown that government-provided insurance through Medicare or Medicaid and lower socioeconomic status are markers of clinical risk but also of poorer access to primary care relative to those with private insurance. 6,[15][16][17][18][19][20] Future work must separate the association of increased clinical risk from the direct association of access to care and medical management with various insurance types. Together, our findings suggest that PPRs after surgery represent a significant burden to the US health care system and that interventions to improve PPR rates may be targeted to patients with significant underlying comorbidities as well as those undergoing high-risk operations.…”
Section: Discussionmentioning
confidence: 99%